Modern Tools in Education Used within the Technical Mechanics Lessons. (12th February 2015) - Monkova, Katarina; Monka, Peter; Hutyrova, Zuzana; Cizikova, Andrea
Abstract: The article deals with the using of modern tools in education within the Technical mechanics lessons, especially in the scope of kinematic and dynamic analysis of mechanism. It is focused on the possibility to solve the same problem by three various approaches. Students are firstly acquainted with basic mechanical principles and after problem solution they can compare not only achieved results but also the advantages and disadvantages of individual methods. It can be said that most popular technique is solution using computer aid, because traditional methods require numerical computation and students have the limitations in math. On the other hand the teacher's task is to show to students that the modern tools help us to simplify and shorten the problem solving but the know-how has to provide user of software. So the theoretical base and traditional methods used in education process have in some cases their justification.